Pain Tolerance in Persons With Recognized and Unrecognized Myocardial Infarction: A Population‐Based, Cross‐Sectional Study - Andrea Milde Øhrn; Christopher Sivert Nielsen; Henrik Schirmer; Audun Stubhaug; Tom Wilsgaard; Haakon Lindekleiv (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Unrecognized myocardial infarction (MI) is a prevalent condition associated with a similar risk of death as recognized MI. It is unknown why some persons experience MI with few or no symptoms; however, one possible explanation is attenuated pain sensitivity. To our knowledge, no previous study has examined the association between pain sensitivity and recognition of MI. Methods and Results We conducted a population‐based cross‐sectional study with 4849 included participants who underwent the cold pressor test (a common experimental pain assay) and ECG. Unrecognized MI was present in 387 (8%) and recognized MI in 227 (4.7%) participants. Participants with unrecognized MI endured the cold pressor test significantly longer than participants with recognized MI (hazard ratio for aborting the cold pressor test, 0.64; CI, 0.47–0.88), adjusted for age and sex. The association was attenuated and borderline significant after multivariable adjustment. The association between unrecognized MI and lower pain sensitivity was stronger in women than in men, and statistically significant in women only, but interaction testing was not statistically significant (P for interaction=0.14). Conclusions Our findings suggest that persons who experience unrecognized MI have reduced pain sensitivity compared with persons who experience recognized MI. This may partially explain the lack of symptoms associated with unrecognized MI.